2012
DOI: 10.1371/journal.pone.0033611
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poor CD4 and Weight Recovery in HIV-Infected Children Initiating ART in South Africa

Abstract: ObjectiveTo identify baseline demographic and clinical risk factors associated with poor CD4 and weight response after initiation of antiretroviral therapy (ART) in a cohort of human immunodeficiency virus (HIV)-infected children in KwaZulu-Natal, South Africa.MethodsWe performed a retrospective cohort study of 674 children initiating antiretroviral therapy at McCord and St. Mary's hospitals in KwaZulu-Natal, South Africa, from August 2003 to December 2008.We extracted data from paper charts and electronic med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
6
17
0
Order By: Relevance
“…This might be justified by too depleted thymus and other lymphoid tissues to repopulate the T lymphocytes after initiation of ART in older age groups. On the other hand, in our study there is no relationship between gender of the patient and risk of adverse immune restoration though other studies were with discordant results; some reported male gender is associated with poor immune recovery others showed no gender difference [14][15][16]. Presence of chronic diarrhea during ART treatment is associated with poor CD4 cell recovery independent of nutritional status of the patient which is in agreement with most previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…This might be justified by too depleted thymus and other lymphoid tissues to repopulate the T lymphocytes after initiation of ART in older age groups. On the other hand, in our study there is no relationship between gender of the patient and risk of adverse immune restoration though other studies were with discordant results; some reported male gender is associated with poor immune recovery others showed no gender difference [14][15][16]. Presence of chronic diarrhea during ART treatment is associated with poor CD4 cell recovery independent of nutritional status of the patient which is in agreement with most previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Baseline and nadir CD4 counts are major determinants of CD4 cell recovery after ART initiation [32][33][34][35][36][37][38], so individuals with higher CD4 cell counts starting ART will recover more cells. This has led to African Ministries of Health progressively increasing the target CD4 cell count for when to start antiretrovirals.Age is a well-recognized factor influencing CD4 cell count recovery [39][40][41][42], resulting in the 2012 Department of Health and Human Services (DHHS) guidelines recommending ART for all individuals over 50 years old, irrespective of CD4 cell count.Haemoglobin, a valuable indicator of health status, has been reported to be associated with CD4 cell reconstitution [43] and with survival in HIV-infected individuals [44]. Many studies looked at baseline haemoglobin at the start of therapy, but we found that the increase in haemoglobin from baseline to the time of the study visit was a better indicator of CD4 cell recovery than baseline or study visit haemoglobin levels alone.…”
mentioning
confidence: 65%
“…In retrospective study involving 1186 children in Ethiopia, Bacha et al found that chronic malnutrition was an independent predictor of first-line ART failure in children under 3 years of age [17]. In a study by Zanoni et al from South Africa, chronic diarrhea at baseline, independent of nutritional status and viral response, was predictive of poor CD4 recovery [70]. Given the relatively low cost and feasibility of nutritional supplementation, further exploration of its potential role in improving health outcomes in HIV-infected children is needed.…”
Section: Malnutritionmentioning
confidence: 99%